(untitled) (Heritage, 2023)
Safety management is a new scientific discipline that was created by merging two sciences, safety science and management science. Modern security threats, which have been increasing recently, have led to an increased interest in security issues, as well as in organizations that deal with these issues. In accordance with the changes that have occurred in the field of security, different theories and schools of security have also developed and changed. The aim of this paper is, therefore, to present different approaches in the study of security management as a scientific discipline, and to point out the similarities and differences between the presented theories and schools. The paper presents the traditional - voluntarist approach and alternative approaches to security. Contemporary problems of safety management with the challenges ahead are also given.